ANALISIS MOTIVASI BELAJAR SISWA SMP KELAS VII MENGGUNAKAN MEDIA VBA FOR EXCEL PADA MATERI ARITMATIKA SOSIAL - Afina Aulia Urrifa Duaely; Martin Bernard (IKIP Siliwangi, 2022)
Social arithmetic is a very important mathematical material to be studied because it is concerned with everyday life. But in reality many students do not understand the concept of social arithmetic well so the need for VBA for Excel as a medium of learning to motivate students in learning social arithmetic. This study aims to analyze student’s learning motivation in the use VBA for Excel media on social arithmetic material. This research was conducted by using the qualitative descriptive research method. The subject of this research was a class VII junior high school student of 5 people, consisting of 2 male students and 3 female students. The instrument used in this study was a learning motivation indicators that amounted to 5 indicators and consisted of 10 positive and negative statements scale. The data processing technique used is the percentage scale of a student’s learning motivation attitude with the help of the Likert scale. This research indicated that learning using VBA for Excel media produces positive. These results can be seen from the average student response including strong categories, with a percentage of 68,5%.